Michael Z. Vinokouroff papers - Vinokouroff, Michael Z., 1894-1983.
A bound file relating to the career of the Reverend George Vinokouroff in Sitka, Alaska, (1851-1863), and selections (1927-1930) from a bound volume relating to the acquisition of the Alaskan Russian Orthodox Church records by the Library of Congress.
Microfilm produced from originals in private hands.
Clergyman.
Collection material in Russian.
Collection related to the Library of Congress Archives.
Keywords: Vinokourov, George; Library of Congress; Russian Orthodox Greek Catholic Church of America. -- Diocese of Alaska; Church records and registers -- Alaska -- Sitka; Clergy